HUBUNGAN ANTARA POLA ASUH DAN KEPATUHAN DIET BEBAS GLUTEN BEBAS CASEIN DENGAN STATUS GIZI ANAK AUTIS DI KOTA PONTIANAK - Suharningsih, Suharningsih; Marlenywati, Marlenywati; Budiastutik, Indah (Fakultas Ilmu Kesehatan Universitas Muhammadiyah Pontianak, 2015)
Background : Autism is a complex developmental and interrelated disorder that dincludes breakdown in communication, social interaction, and emotion. A preliminary survey conducted at Sekolah Cahaya Bangsa, Sekolah Bina Anak Bangsa and Autism center showed that 56% out of 18 children had abnormal nutrition (consisting of 50% malnutrition status, and 6% nutritional status), with an average of bad upbringing and BGBC compliance. The aim of this study was to determine the correlation of parenting, compliance with a gluten-free casein-free diet and nutritional status of children with autism in Pontianak.Objective : This study aimed at finding out the correlation of history of Diabetes, hypertension, smoking, toards cataract cases among unit’s patients of Dr. Soedarso hospital.Method : Using observational analytic and cross sectional design, this study employed 64 respondent. The samples were 55 children selected by using sampling incidental technique. This sampling technique was based in the inclusion and exclusion criterias. The data were tested by using Chi Square test.Result : The statistical analysis reveald that there were correlation of parenting (p value = 0,007 and PR = 2.500), food / nutrition parenting (p value = 0.014 and PR = 2.319), hygiene parenting (p value = 0.000 and PR = 3,500) , health care pattern (p value = 0.020 and PR = 2.342), compliance with a gluten-free casein-free diet (p value = 0.024 and PR = 2.231) and nutritional status of children with autism in Pontianak. There was no correlation of recreation parenting and nutritional status of children with autism in Pontianak (p value = 0.070 and PR = 1.891).Sugesstion: Based on findings, Health departement of Provinsi specially Health Departement Kota Pontianak is encouraged to monitoring the children’s growth and development in term of both parenting cand gluten-free casein diet; so that normal nutritional statusluten-free casein-free diet can be achieved.Keywords : Autism,parenting, gluten-free casein-free diet, nutritional status